Profile of Research Skills of Class X High School Students on Environmental Change Material - Dini Nurani Rahmawati; Diana Rochintaniawati; Mimin Nurdjani Kusumastuti; Eni Nuraeni; Riandi Riandi (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
This study aims to (1) observe biology learning activities on environmental change and (2) analyze the level of research skills of high school students on the concept of environmental change. This research used a descriptive qualitative method with a case study approach to understand an issue or problem using a case within a certain period by collecting data from various sources such as observation, interviews, and documents. The data collection technique used was non-participant. The instrument used in this study was an observation sheet to observe learning activities carried out by the teacher. In addition, interviews were conducted with teachers, and questionnaires were given to students to obtain information on the extent to which teachers and students know research skills and to see the level of research skills possessed by students. The research results show that the teacher’s learning process has not directed students to develop research skills, so the research skills profile in the sample studied is still lacking and not optimal.